Step-Ladder Expansive Cranioplasty after Decompressive Craniotomy and Expansive Duraplasty: Discussing Possibilities on a Mathematical Model - Sengupta, S. K. (Indian Journal of Neurosurgery, 2015)
Background Role of decompressive craniectomy in reducing intracranial pressure is well established. However, it comes with a cost of requiring a second surgery in the form of cranioplasty without which unacceptable hemodynamic consequences occur. It is generally felt that a credible alternative is required.Objective The aim of the study is to devise a mathematical model, which closely represents the cranium and intracranial contents, on which various alternatives can be evaluated with reproducible results, and to work out the effects of a novel technique of expansive cranioplasty on that model.Methods A mathematical model was designed based on the presumption that dura forms a watertight bag-containing brain, floating in cerebrospinal fluid (CSF). A model for an expansive cranioplasty was designed, and its ability to provide the space required to allow volume expansion and to achieve adequate reduction in intracranial pressure (ICP) was evaluated on this model.Results The mathematical model could closely reproduce the surface area–volume relationships in the published literature. Based on the calculations on the model, it was found that a projection of dural outpouching of 0.83 cm beyond the craniectomy margin on either side of a bilateral 12 × 15 cm elliptical craniectomy defect is required to achieve and accommodate a volume expansion of 157 cm3, which was recorded to be the maximum volume expansion in the reviewed literature. A two-step step-ladder cranioplasty can be constructed to achieve an increase in cranial width by 1.1 to 1.3 cm on each side.Conclusion Calculations based on the present model indicate that a two-step expansive cranioplasty can accommodate adequate volume expansion while alleviating the ill effects of a craniectomy and necessity of a second surgery. However, these are discussions on mathematical model, based on multitude of assumptions and approximations, and hence these discussions require clinical trials to validate the findings.
Keywords: decompressive craniotomy; step-ladder expansive cranioplasty; mathematical model